2017
DOI: 10.1186/s12877-017-0446-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug-based pain management for people with dementia after hip or pelvic fractures: a systematic review

Abstract: BackgroundStudies indicate that people with dementia do not receive the same amount of analgesia after a hip or pelvic fracture compared to those without cognitive impairment. However, there is no systematic review that shows to what extent drug-based pain management is performed for people with dementia following a hip or pelvic fracture.The aim of this systematic review was to identify and analyse studies that investigate drug-based pain management for people with dementia with a hip or pelvic fracture in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…Our study revealed that patients with severe/very severe or unbearable pain are at higher risk of developing malnutrition risk than those without pain. As a result, an adequate assessment of pain can be considered as the first step towards providing help and improving the pain management practice ( 15 , 32 , which can help reduce consequences of pain like malnutrition. The accurate assessment of pain is a great challenge, because pain cannot be easily measured using a single biological marker ( 35) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed that patients with severe/very severe or unbearable pain are at higher risk of developing malnutrition risk than those without pain. As a result, an adequate assessment of pain can be considered as the first step towards providing help and improving the pain management practice ( 15 , 32 , which can help reduce consequences of pain like malnutrition. The accurate assessment of pain is a great challenge, because pain cannot be easily measured using a single biological marker ( 35) .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pain assessment scales are available, but pain assessment is not performed routinely ( 10 , 36 , 37 . This has been described as a substantial barrier to the accurate treatment of older people with pain ( 32 , 33 . Furthermore, older patients may attempt to avoid to taking too many pain killers, because they may be afraid of adverse effects or addiction.…”
Section: Discussionmentioning
confidence: 99%
“…However, while there are numerous assessment scales available, pain assessment is not performed routinely [12,23]. The low use of pain assessment scales has previously been described as a substantial barrier against the accurate treatment of older people with pain and dementia [21,22]. Care professionals acknowledged lack of knowledge has also been identified as a fundamental barrier to optimal pain management [9,11].…”
Section: Aq4mentioning
confidence: 99%
“…This could be related to the population here described, as one of the exclusion criteria was severe dementia, which implies an impossibility to autonomously and reliably evaluate pain. A meta-analysis by Moschinski et al [ 22 ] reports that postoperative morphine consumption could be significantly different in demented patients compared to non-demented. Finally, one of the other potential reasons for the absence of a statistically significant difference on the primary endpoint concerns the way the blocks were performed.…”
Section: Discussionmentioning
confidence: 99%